Analisis Faktor Penghambat dalam Perkembangan Kecerdasan Interpersonal Anak di Taman Kanak-kanak - Desi Karmila; Delfi Eliza (Universitas Negeri Padang, 2021)
Interpersonal intelligence is very important for children to be easily accepted in the community because children with interpersonal intelligence have many skills, namely the ability to empathize (sharing, helping and helping others), the ability to recognize other people's thoughts, the ability to make friends, and establish social relationships so that they can build relationships. positive relationships with others. Some of the inhibiting factors for children's interpersonal intelligence include the child's individual home environment, parenting patterns that are too authoritarian and overprotective. Therefore, teachers and parents should pay attention to every development and interpersonal intelligence of children so that children have good interaction skills in their daily lives